Mitochondrial ultrastructure and function in the oxygen deprived rat heart : effects of therapeutic intervention - Edoute, Yeouda (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D. (Medical Sciences)) -- University of Stellenbosch, 1980.